Protection of Press Freedom through Strengthening Law Number 40 of 1999 in The Context of the Enforcement of Law Number 1 of 2023 - Rina Rohayu Harun; Nurjannah Septyanun (Faculty of Law, Universitas Pekalongan, 2025)
Press freedom for journalists has become increasingly restricted following the enactment of the National Criminal Code, Law No. 1 of 2023, by the government, raising concerns about the potential criminalization of journalists performing their duties. Several articles in the National Criminal Code (New Criminal Code) have been noted by the Press Council, one of which pertains to the broadcasting or dissemination of false news or information. The term 'any person' in the relevant article can apply to anyone, including journalists. Meanwhile, responsible and proper press freedom has already been accommodated through a specific law, namely Law No. 40 of 1999. The problem addressed in this study is how press freedom, based on Law No. 40 of 1999, relates to press offenses as regulated by Law No. 1 of 2023. The method used in this study is normative juridical, supported by empirical juridical analysis. The research findings indicate that even before the National Criminal Code was enacted, several journalists, including in the case of Asrul, were criminalized for allegedly spreading false news under the Electronic Information and Transactions Law (ITE Law). There is concern that the National Criminal Code could also be used by law enforcement to target journalists engaged in their journalistic profession. Therefore, revisions to certain articles in the National Criminal Code are necessary to provide exemptions for the journalistic profession, which is protected by the press law, and to establish a specific mechanism to be prioritized in the event of a press dispute.